2020
DOI: 10.1152/ajprenal.00598.2019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal hemodynamic changes in a female mouse model of systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic multisystem autoimmune disease characterized by circulating autoantibodies, prevalent hypertension, renal injury, and cardiovascular disease. Onset of the disease often occurs in young women of childbearing age. Although kidney involvement is common to patients with SLE, little is known about temporal changes in renal hemodynamic function and its relationship to the pathogenesis of hypertension during autoimmune diseases. We hypothesized that the loss of immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
1
4
0
1
Order By: Relevance
“…While there are limited data on the renal effects of leptin antagonism, a very recent study in pigs showed that antagonism of leptin prevents inflammation in a porcine model of ischemia reperfusion [ 91 ]. As we have previously published, the rates of albuminuria vary in this model of SLE [ 37 , 39 , 92 ], and treatment with LA did not improve albumin excretion despite improving glomerular injury ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 56%
“…While there are limited data on the renal effects of leptin antagonism, a very recent study in pigs showed that antagonism of leptin prevents inflammation in a porcine model of ischemia reperfusion [ 91 ]. As we have previously published, the rates of albuminuria vary in this model of SLE [ 37 , 39 , 92 ], and treatment with LA did not improve albumin excretion despite improving glomerular injury ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 56%
“…Total lymphoid irradiation has been reported to prolong the survival, reduce proteinuria, and decrease anti-DNA antibody levels in NZBWF1 [ 17 , 47 , 48 ] and MRL/1 mice [ 18 ], but the mechanisms underlying these effects remain to be clarified. These reports implicated that the immune system was concerned with the alleviation of SLE-like morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Jennifer Sasser (University of Mississippi Medical Center) is recognized as an expert in the renal adaptions to pregnancy (14,51). Her group has characterized the Dahl salt-sensitive rat as a model of preeclampsia that closely mimics the human disease.…”
Section: Promoting Diversity and Inclusionmentioning
confidence: 99%